The Tradition of Brushing Teeth with Betel Nut Peel with Abrasion Incidents in the Salele Community Tilomar Timor Leste Country - Santana Martins; Francisca Fatima de Sena (Jurnal Kesehatan Gigi, 2022)
ABSTRACTSalele Timor Leste people have long known betel leaf, betel nut, and lime as ingredients for betel or toothbrush. The behavior of brushing teeth with betel nut peel is one way to take care of teeth which was believed by the ancestors. There are positive and negative effects on dental health. From a positive point of view, it inhibits the process of caries formation, while the negative effects of brushing teeth with betel nut peel on the teeth and gums can cause discoloration of the teeth (stain), periodontal disease on the oral mucosa, lesions on the oral mucosa, poor oral hygiene,  atrophy of the tongue mucosa and can cause abrasion.This research is an analytic observational study with a cross-sectional approach. The sample size used is 25 respondents with purposive sampling technique. The data were analyzed by univariate analysis (frequency distribution) and bivariate analysis (rank Spearman correlation test) to determine the relationship between the traditional habit of brushing teeth with betel nut peel on the incidence of abrasion. The results showed that there was a significant relationship between the tradition of brushing teeth with betel nut peel on the incidence of tooth abrasion. The frequency of brushing your teeth with betel nut peel more than twice a day can have bad effects on oral and dental health.